Age Determination of Pheasants (Phasianus Colchicus) using Discriminant Analysis - Maureen I.A. Woodburn; John P. Carroll; Peter A. Robertson; Andrew N. Hoodless (National Quail Symposium Proceedings, 2017)
Most gallinaceous birds can be identified as juveniles or adults using the outermost primaries (P9 and P10) which are retained until after the first breeding season and are often identifiable by colour and wear. The pheasant Phasianus colchicus, however, moults all ten primary feathers during its post-juvenile moult so alternative techniques are required. To date the method most widely used on live birds is measurement of the shaft diameter of the proximal primary feather, P1, which is replaced first before the bird is fully-grown. Using a known-age sample of 752 free-living pheasants, this study presents a discriminant function analysis using proximal primary feather measurements and other morphological characteristics to achieve a greater level of accuracy of ageing. Ageing accuracy was high, especially for males, at over 95%. The model was less accurate for females, with 83% and 94% respectively for the two year groups. When our model was applied to an independent data set of unknown-age birds 85% were classified. Less than 3% could not be aged accurately and the remainder were unclassified due to missing measurements. Our model offers a reliable method of ageing pheasants, both live and dead, however researchers are cautioned to potential year, origin (stock) and site effects.
Keywords: ageing; discriminant function analysis; Phasianus colchicus; proximal primary feather; pheasant